Kontribusi Kegiatan Komunitas Pasukan Amal Kebaikan dalam Membetuk Akhlak Mahmudah Masyarakat Modern di Kabupaten Jember - Hasanuddin; Nahrowi, Moh. (Kartika: Jurnal Studi Keislaman, 2025)
This research seeks to evaluate the role of the Good Deeds Troop Community’s activities in fostering virtuous character within modern society in Jember Regency, focusing on three core aspects: the relationship with God (Hablu Min Allah), interpersonal relationships (Hablu Min Annas), and the relationship with the natural environment (Hablu Min al-Alam). The central issue addressed in this study is the extent to which community initiatives contribute to shaping positive character in the midst of rapid modernization. Utilizing a qualitative approach through a case study method, data were gathered from in-depth interviews, direct observations, and documentation involving both community members and local residents. The findings demonstrate that the community's activities significantly enhance spiritual practices and religious awareness (Hablu Min Allah), reinforce social values such as cooperation and mutual care (Hablu Min Annas), and encourage environmental responsibility (Hablu Min al-Alam). This study highlights that active participation in community-based initiatives plays a crucial role in cultivating noble character traits that align with both religious teachings and societal values prevalent in Jember Regency.